Public Pensions and Collective Bargaining Rights: Evidence from State and Local Governments. (24th March 2018) - Hoang, Trang; Goodman, Doug
Abstract: An aging workforce and increasing retirement benefits are ongoing problems for states and municipalities. Unions are often blamed for governments offering too generous pension benefits. This contributes to budgetary pressures in some state and municipal governments. This article analyzes the impact of collective bargaining on pension benefit generosity under different economic conditions. The study finds that the impact of collective bargaining on pension benefits is not consistent over time or across pension plans. Collective bargaining has a positive effect on pension benefits under worsening economic conditions. Additionally, unions indirectly influence pension benefit generosity through campaign donations and unionization intensity. The findings suggest mixed impacts of collective bargaining on different groups of public employees regarding pension contributions. The article concludes with implications for the role of unions in public financial performance and strategic human resource management during fiscal austerity .